Audit Entitas Kecil dan Menengah serta Penggunaan Cloud dalam Berbagi Data (Studi Kasus pada Kantor Akuntan Publik ABC) - Satria Chandra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to implement a special audit manual for small and medium-sized entities (SME) and the application of the cloud in the audit process to improve the efficiency of financial statement audits by small and medium-sized practitioners (SMP). This a qualitative research with a case study approach in a public accounting firm in Indonesia (KAP). The design of the audit manual and the use of the cloud in this study has been designed by the authors in previous research. The cloud can speed up the audit process through easy data sharing, electronic data archives, and teamwork monitoring. In addition, the scalability of using the cloud can help SMPs increase their productivity. The scope of the implementation manual design is only at the risk assessment stage. Applying the cloud in the audit process only uses the free features of the service provider. The results of the study helped SMPs to implement a simple audit manual and use the cloud to increase the audit efficiency of SMEs. This study pays great and specific attention to the audit of SMEs. The majority of the audit research studies concentrate on big audit firm practices.